Introduction to finite element analysis : formulation, verification, and validation - Szabo, B. A. (Barna Aladar), 1935-; Babuska, Ivo.; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley, 2011)
"The authors believe that users of finite element analysis (FEA) software products must have a basic understanding of how mathematical models are constructed; what are the essential assumptions incorporated in a mathematical model; what is the algorithmic structure of the finite element solution; how the accuracy of the computed data can be assessed, and how to avoid common pitfalls and mistakes. The primary objective in assembling the material presented in the book is to provide a basic working knowledge of the finite element method. A professional quality software product will also be made available to the reader providing over 400 parameter-controlled examples of solved problems."--
"The primary objective in assembling the material presented in the book is to provide a basic working knowledge of the finite element method"--
Front Matter -- Introduction -- An Outline of the Finite Element Method -- Formulation of Mathematical Models -- Generalized Formulations -- Finite Element Spaces -- Regularity and Rates of Convergence -- Computation and Verification of Data -- What Should be Computed and why? -- Beams, Plates and Shells -- Nonlinear Models -- Appendix A: Definitions -- Appendix B: Numerical Quadrature -- Appendix C: Properties of the Stress Tensor -- Appendix D: Computation of Stress Intensity Factors -- Appendix E: Saint-Venant's principle -- Appendix F: Solutions for Selected Exercises -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Finite element method; TECHNOLOGY & ENGINEERING -- Drafting & Mechanical Drawing; Finite element method; Electronic books